Determinants That Influence the Community's Voting Sharia Financial Technology (Fintech) - Nuhwana Saputra, Mohammad (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
In the Digital Age, many activities are carried out using technology, such as making telephone electricity payments, shopping with e-commerce, including applying for loans, so that technology is a community need, especially those who have high mobility. The purpose of this study was to examine the effect of the variables financial literacy, religiosity and the Technology Acceptance Model on the decision to choose financial technology financing. The object of research is the people living in Jabodetabek, with a quantitative descriptive design. The research data source is primary data obtained by distributing questionnaires to respondents. The population of people who live in Jabodetabek with the sample selection technique using purposive sampling of 105 respondents. Data analysis used Structural Equation Modeling (SEM) with PLS 3.0 software. The research results prove that the literacy variable based on the P-Value value is obtained 0.00 <0.05, meaning that the literacy variable has a significant effect on the dependent variable in the decision to choose sharia fintech. Based on the P-Value, the Religious Variable is 0.00 <0.05, meaning that the Religious variable has a significant effect on the dependent variable on the decision to choose Islamic fintech. Meanwhile, the Technology Acceptance Model variable based on the P-Value value obtained 0.602 > 0.05, meaning that the Technology Acceptance Model variable has no significant effect on the dependent variable on the decision to choose Islamic fintech. meaning that the Literacy variable has a significant effect on the dependent variable on the decision to choose sharia fintech. Based on the P-Value, the Religious Variable is 0.00 <0.05, meaning that the Religious variable has a significant effect on the dependent variable on the decision to choose Islamic fintech. Meanwhile, the Technology Acceptance Model variable based on the P-Value value obtained 0.602 > 0.05, meaning that the Technology Acceptance Model variable has no significant effect on the dependent variable on the decision to choose Islamic fintech. meaning that the Literacy variable has a significant effect on the dependent variable on the decision to choose sharia fintech. Based on the P-Value, the Religious Variable is 0.00 <0.05, meaning that the Religious variable has a significant effect on the dependent variable on the decision to choose Islamic fintech. Meanwhile, the Technology Acceptance Model variable based on the P-Value value obtained 0.602 > 0.05, meaning that the Technology Acceptance Model variable has no significant effect on the dependent variable on the decision to choose Islamic fintech.